Atypical Disseminated Zoster in a Patient With Unrecognized Severe Hypogammaglobulinemia - Nathan Walton; Eyas Alzayadneh; Robert Robinson; Rachael Stadlen; Rolando Sanchez (Annals of Internal Medicine: Clinical Cases)
A 74-year-old woman with history of chronic myeloid leukemia status post matched unrelated donor allogenic hematopoietic stem cell transplant in remission for 23 years was transferred to the intensive care unit with diffuse purpuric rash, progressive lethargy, shock, and multiorgan failure. She had presented to a local hospital a few days before admission with severe epigastric pain, radiating to her chest and back. Laboratory work-up revealed multiorgan failure, cytokine storm consistent with hemophagocytic lymphohistiocytosis, and severe hypogammaglobulinemia. Despite supportive management the patient's condition deteriorated, and she died. The skin biopsy and autopsy demonstrated disseminated varicella zoster with widespread leukocytoclastic vasculitis.